Humedales artificiales: una alternativa para tratamiento de aguas de producción (2018)
The purpose of this monograph is to publicize artificial wetlands as one of the possible efficient and economical treatment options for the production waters of the oil industry. Phytoremediation is a technique in which plants are used to eliminate contaminants present in water, an economical and friendly alternative to the environment, different from some conventional treatment methods already used. The study presents the types of artificial wetlands that exist, cases in which this technology has been implemented outside the country and a pilot experience in Colombia with production waters with their respective results, as well as the parameters that must be taken into account in the time to treat water, the comparison of costs, advantages and disadvantages between an artificial wetland and a conventional treatment process and the variables to include in the design of an artificial wetland.